Arabic Handwriting Word Recognition Based on Scale Invariant Feature Transform and Support Vector Machine - Abdul Hassan, Alia Karim; Mahdi, Bashar Saadoon; Mohammed, Asmaa Abdullah (Iraqi Journal of Science, 2019)
Offline Arabic handwritten recognition lies in a major field of challenge due to the changing styles of writing from one individual to another. It is difficult to recognize the Arabic handwritten because of the same appearance of the different characters. In this paper a proposed method for Offline Arabic handwritten recognition. The proposed method for recognition hand-written Arabic word without segmentation to sub letters based on feature extraction scale invariant feature transform (SIFT) and support vector machines (SVMs) to enhance the recognition accuracy. The proposed method experimented using (AHDB) database. The experiment result show (99.08) recognition rate.